Nutritional quality assessment and antiplasmodial activity of Cajanus cajan (L.) Huth., Crescentia cujete L. and Myrianthus preussii Engl. from Akure, Southwestern Nigeria - Titus Adeniyi Olusi; Mojirayo Rebecca Ibukunoluwa; Ebenezer Oluyemi Dada (International Journal of Phytomedicine, 2015)
Background and Purpose of the Study: Many plants are now considered to have dual purpose usefulness in terms of their therapeutic effects and nutritional benefits. Cajanus cajan (L.) Huth., Crescentia cujete L. and Myrianthus preussii Engl. are combined for use in the treatment of malaria in Akure, Southwestern Nigeria. Materials and Methods: The powdered plant samples were screened for phytochemical constituents, proximate composition and mineral elements according to standard protocols. Plasmodium berghei infected mice were administered with water and ethanol extracts of plant samples and blood samples screened for parasitemia. Data were statistically analyzed. Results: Alkaloids, glycosides, saponins, tannins, and polyphenols were present in all the three samples. Anthraquinones and flavonoids were altogether absent. C. cajan had the highest ash (11.69%), crude protein (17.76%) and fat (17.34%) whereas C. cujete was richest in carbohydrate (58.52%). Calcium was found to be highest in C. cujete (22672.43mg/kg) and least in C. cajan (13288.33mg/kg). C. cujete was richest (898.37mg/kg) and C. cajan (304.22mg/kg) least in iron. However, magnesium was found to be highest in M. preussii (5837.03mg/kg) and least in C. cujete (2166.48mg/kg). The ethanol extract of the recipe was most active at 200mg/kg. Conclusions and Application of Findings: Dietary or mineral elements serve structural, functional and biochemical roles. The three plants contained appreciable major and minor elements. The leaf of C. cajan could serve as a complement for animal protein. The activity observed in the ethanol extract could be as a result of the complete dissolution of the phytochemicals in ethanol. Toxicity studies on the plants will confirm their safe application, although lead tested negative in the plant samples.